Are We Ready for Newborn Genetic Screening? A Cross-Sectional Survey of Healthcare Professionals in Southeast China - Wu, Xian; Yang, Yuqi; Zhou, Lingna; Long, Wei; Yu, Bin (Frontiers in Pediatrics, 2022)
Objectives: To understand the knowledge, attitude, willingness, and ability of healthcare professionals working in newborn screening centers regarding newborn genetic screening (nGS). Methods: The questionnaire consisted four sections with 27 questions and the data were collected by WJX platform. All participants accessed the questionnaire by scanning a specific QR code with their mobile phones. Two researchers completed the summary and analysis independently. Results: A total of 258 valid questionnaires were collected from 43 newborn screening centers in six provinces of Southeast China. 209 (81.01%) participants were interested in nGS and almost all participants (97.67%) thought that nGS was necessary in China. 89.53% of participants thought that it could be used to effectively expand the diseases that could be screened, but 72.87% also worried about the inability to provide genetic counseling. 55.34% suggested that nGS and tandem mass spectrometry (TMS) screening could be applied in unite screening mode. The higher the institution level and personal education level, the higher the interest healthcare professionals displayed towards nGS. However, they also showed greater concern about the inability to provide genetic counseling and ethical issues. If a center had engaged in TMS screening, its staff would be more likely to believe that nGS had great advantages. Most participants also had ethical concerns, such as “Psychological burden caused by carrying information regarding adult morbidity risk. Conclusion: Most participants were interested and considered nGS necessary. The inability to provide genetic counseling may be the primary impediment to clinical practice. Three important influencing factors were level of education, institution level and engagement in TMS screening.